Lyapunov functions and global stability for SIR and SEIR models withage-dependent susceptibility - Andrey V. Melnik; Andrei Korobeinikov (Mathematical Biosciences and Engineering)
We consider global asymptotic properties for the SIR and SEIRage structured models for infectious diseases where the susceptibilitydepends on the age. Using the direct Lyapunov method with Volterratype Lyapunov functions, we establish conditions for the global stabilityof a unique endemic steady state and the infection-free steady state.